Boys, Books and Homophobia: Exploring the practices and policies of masculinities in school - Kehler, Michael (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
Disturbed by a proliferation of quick-fix literacy strategies to “help the boys” increase achievement levels in the midst of a policy shift that acknowledges gay, lesbian, bi and transgender, questioning (GLBTQ) youth, the author examines how masculinities are connected to literacy practices and negotiated through a safe school policy. He argues that specific literacy strategies recommended in recent support documents for teachers are limiting and restrictive because of a narrow view connecting gender and masculinity to literacy practices that reinscribe heteronormative masculinity in schools. He further argues that strategies to increase literacy achievement levels among boys run contrary to a more embracing school board policy aimed at acknowledging diverse multiple youth identities.